“The Force of All Our Numbers”: New Leftists, Labour, and the 1973 Artistic Woodwork Strike - Milligan, Ian (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2010)
Abstract Through late 1973, the Artistic Woodwork strike captivated not only the left-wing milieux of Toronto – from young New Leftists, to rank-and-file union members, to activists from a plethora of political groups – but also the entire city. Artistic was a first contract strike by immigrant workers organized by the Canadian Textile and Chemical Union (ctcu). The narrative of the strike came to be dominated by supporters after many of the workers picketing left due to both fear and the availability of alternative employment. By November, mass pickets of four hundred people added to political pressure and helped secure a first contract settlement. Coming at the end of a period of intense political debate and discussion concerning the agent of social change and the role of the working-class, Artistic assumed special significance in the personal trajectories of many supporters. On these violent picket lines, supporters had an opportunity to act out the prevailing Marxist sociology of the time. Artistic demonstrates the confluence of a variety of forces at the end of the long sixties: the widespread turn towards Marxism and the working-class as a necessary component of social and political change; the importance of nationalism as a unifying feature between some New Leftists and unions such as the ctcu; and the continuing social responsibility of the student and the intellectual. While Artistic was decertified in 1975, we can take valuable lessons from the strike concerning the impact of allowing strikebreakers as well as the power and importance of a social network in garnering widespread strike support.